Soil management of limed areas cultivated with banana identified by magnetic susceptibility - Pinto de Matos, Alex; Sidney Rocha Matias, Sammy; Sidney Rocha Matias, Sammy; Lopes Nunes, Régia Karolyny; Marques Morais, Estefenson; Saraiva Tavares Filho, Gilberto (Revista Ceres, 2023)
The geostatistics technique is widely used to identify the variability of soil attributes, although being expensive due to the large number of samples that it requires. In this sense, magnetic susceptibility has been an alternative to assess landscape variation, a fact that can assist in sampling planning. This study aimed to evaluate the potential of magnetic susceptibility in identifying specific soil management zones and its relationship with soil attributes that can assist in the management of correction and fertilization in an area cultivated with banana with limestone application modes. In a banana orchard, 42 soil samples were collected at a depth of 0.00 to 0.20 m, with a 30 x 35 m sampling grid. The attributes evaluated were magnetic susceptibility, pH, organic matter, aluminum, H + Al, base saturation and cation exchange capacity, clay, sand, and silt. A descriptive and geostatistical analysis of the data was performed. Spearman correlation analysis was used to identify which attributes are associated with magnetic susceptibility. Magnetic susceptibility correlates with chemical and granulometric attributes in the Entisols. Magnetic susceptibility proved to be an efficient attribute in identifying specific management zones, assisting in the sampling planning of soils cultivated with banana.